(untitled) (Journal of Human Sciences, 2022)
Maqamat art is one of the interesting anecdotal arts, as it carries a guiding message for the Arab community at the time. This art, which appeared at the hands of one of the greatest writers of that era - Badi’ al-Zaman al-Hamdani - received great interest from the general public at that time, not only on the Arab level, but it was also transferred and translated into other languages, and through this development books were written that specializes in this art. From this point of view, I chose one of the shrines to study it, an analytical study, using the science of semiotics, and this choice fell on the Harziya shrine. Patience, and the calf person who has nothing of patience will be prey to adversities and calamities, and in this place the Qur’anic intertextuality, poetic intertextuality, and Arab heritage are mixed, so that the writer presents his message in an interesting literary form that enables the reader to benefit from it without getting bored, and in this study we will try to explore What is in this maqam of secrets, and signs refer to reality.